Spiritual Emotional Freedom Technique (SEFT) Intervention on Blood Pressure among Pregnancy with Hypertension - Anggita septyani permatasari; Rr. Sri Endang Pujiastuti; Donny Kristatnto Mulyantoro (Alta Dharma Publisher, 2020)
Pregnant women with hypertension are the most dominant cause of maternal and neonatal mortality in midwifery services. Spiritual Emotional Freedom Technique (SEFT) is a relaxation technique that can provide a relaxed feeling to overcome improve blood flow and reduce blood pressure. The study aimed to examine the effectiveness of giving SEFT to decrease blood pressure in the class of pregnant women with hypertension. A quasi-experimental, pre-test, and post-test with an equivalent control group was applied in this study. We selected 15 respondents using purposive sampling. The SEFT intervention was carried out at 12 points on the body for 1x / day with a duration of 30 minutes for 14 days. The results showed that patients in the experimental group have systolic blood pressure reduction of about 12 mmHg with p-value 0,00. The experimental group has diastolic blood pressure reduction about 12,8 mmHg with p-value 0.00. SEFT given at 12 body points 1x / day with 30 minutes' duration for 14 days proved effective in reducing blood pressure in the class of pregnant women with hypertension. Further research needs to examine SEFT so that other variables related to hypertensive pregnant women can be added by adding a biomarker examination such as Nitric Oxide (NO)